Distribusi Bantuan Bagi Korban Banjir Di Desa Cingkam Aceh Singkil - Khairuddin, Khairuddin; Pohan, Zakirun; Dinata, Muhd. Farabi; Sukriyah, Sukriyah; Haris, Abdul (Abdurrauf Journal of Community Service, 2024)
Community Service (PKM) activities carried out by the PKM STAI Syekh Abdur Rauf Aceh Singkil team are in the form of providing humanitarian assistance to flood victims in Aceh Singkil Regency. The flooded villages are in Gunung Meriah District. The provision of assistance was carried out in flood-prone areas by taking five location points. This location was chosen based on consideration of the conditions and characteristics of flood-prone areas, which are characterized by differences in flood intensity, population number and density, and reliability. The conclusions obtained after this PKM activity are: 1) assistance for basic needs of the community as one of the needs is still very lacking; 2) local government policies on disaster management are still very limited; 3) laws and regulations, especially in the regions, are still limited; 4) Disaster management funding is still highly dependent on the State Expenditure Budget (APBN) and the Regional Expenditure Budget (APBD). Based on this study, it is recommended that it is necessary to determine more carefully the level of participation at each stage of the activity, according to the type of flood management activities. Then the formulation of humanitarian assistance needs to flood victims can be carried out with the recommendation of the local village head. Abstrak: Kegiatan Pengabdian Kepada Masyarakat (PKM) yang dilakukan oleh tim PKM STAI Syekh Abdur Rauf Aceh Singkil berupa pemberian bantuan kemanusiaan korban bencana banjir di Kabupaten Aceh Singkil. Desa-desa yang terendam banjir berada di Kecamatan Gunung Meriah. Pemberian bantuan dilaksanakan pada daerah rawan banjir dengan mengambil lima titik lokasi. Lokasi ini dipilih atas pertimbangan kondisi dan karakteristik daerah rawan banjir, yang dicirikan dengan perbedaan intensitas banjir, jumlah dan kepadatan penduduk, serta keandalan. Simpulan yang diperoleh setelah kegiatan PKM ini adalah: 1) bantuan kebutuhan pokok masyarakat sebagai salah satu kebutuahan masih sangat kurang; 2) kebijakan pemerintah daerah tentang penanggulangan bencana masih sangat terbatas; 3) peraturan perundang-undangan, terutama di daerah masih terbatas; 4) pendanaan penanggulangan bencana masih sangat tergantung dari Anggaran Pendapatan Belanja Negara (APBN) dan Anggaran Pendapatan Belanja Daerah (APBD). Berdasarkan kajian ini direkomendasikan bahwa perlu ditetapkan lebih cermat tingkat partisipasi pada setiap tahap kegiatan, sesuai dengan jenis kegiatan penanggulangan banjir. Kemudian perumusan kebutuhan bantuan kemanusiaan kepada korban banjir dapat dilakukan dengan rekomendasi kepala desa setempat.